2004
DOI: 10.1191/0960327104ht457sc
|View full text |Cite
|
Sign up to set email alerts
|

Four children with colchicine poisoning

Abstract: Colchicine poisoning is a rare event. It is characterized by multiorgan involvement and by poor prognosis associated with overdose. In this article we present four children with colchicine poisoning to emphasize that colchicine poisoning has a large spectrum in childhood. The children's ages ranged between 1 year and 3.5 years. The ingested dosage of colchicine was between 0.37 and 1.72 mg/kg. Most of the findings of colchicine poisoning such as gastrointestinal symptoms, hepatotoxicity, cardiotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 7 publications
1
9
0
2
Order By: Relevance
“…Findings from our study provide strong evidence suggesting that extracellular histones promote regression of hair follicles. Our data, together with data on colchicine-induced hair loss (16,17) and colchicine-driven H4 expression in DP cells (10), provide strong evidence suggesting Following culture of isolated human hair follicles (HFs) in the absence or presence of 20 lg/ml histone H4 and H2A (New England Biolabs, Beverly, MA) for 6 days, gross pictures were taken (a-c). Hair shaft elongation was also measured in the presence of 20 lg/ml concentrations of histone H4 and H2A after cultivation for 6 days (h).…”
Section: Resultsmentioning
confidence: 53%
“…Findings from our study provide strong evidence suggesting that extracellular histones promote regression of hair follicles. Our data, together with data on colchicine-induced hair loss (16,17) and colchicine-driven H4 expression in DP cells (10), provide strong evidence suggesting Following culture of isolated human hair follicles (HFs) in the absence or presence of 20 lg/ml histone H4 and H2A (New England Biolabs, Beverly, MA) for 6 days, gross pictures were taken (a-c). Hair shaft elongation was also measured in the presence of 20 lg/ml concentrations of histone H4 and H2A after cultivation for 6 days (h).…”
Section: Resultsmentioning
confidence: 53%
“…Given that colchicine is the mainstay of treatment in FMF, one may wonder if it can contribute to the liver abnormalities observed in FMF patients. Although hepatotoxicity can occur with colchicine intoxication, doses superior to 5 mg per day, much higher than doses used to treat FMF, are required 69,70 . At the pathophysiological level, animal models have shown that intraperitoneal administration of high doses of colchicine affects Kupffer cell function, leading to reduced toxin clearance 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Crocenzi et al6 demonstrated that in experimental models, colchicine-induced hepatotoxicity depended on the magnitude and composition of the bile salt flux traversing the liver. Ataş et al7 reported the cases of four children who presented with gastrointestinal symptoms, hepatotoxicity, cardiotoxicity and bone marrow suppression after colchicine poisoning. However, no cases of hepatotoxicity resulting from therapeutic doses of either thiocolchicoside or colchicine have been reported.…”
Section: Discussionmentioning
confidence: 99%